KAJIAN YURIDIS PERATURAN OTORITAS JASA KEUANGAN NOMOR I/P.OJK.07/ 2013 TENTANG PERLINDUNGAN KONSUMEN JASA KEUANGAN DI INDONESIA - Dora Kusumastuti (Qistie Jurnal Ilmu Hukum, 2015)
Knowing the concept of legal protection is regulated by Otoritas Jasa Keuangan No. I / P.OJK.07 / Year 2013 abaout  Consumer Protection Financial Services. Research isnormativejuridical and the data taken from secondary data by using interactive analysis model. In aneffort to realize the welfare state, in particular the consumer from the previous position issubordinate to be balanced, the government through the Ototitas Jasa Keuangan No. 1 /POJK.07 / 2013 on Consumer Protection Financial Services Sector, was able to put the position of consumers of financial services to be balanced with the perpetrators of financial services., Keywords: consumer financial services, OJK Regulations